The exploration of fruit flies Bactrocera (Diptera:Tephritidae) and its parasitoid in Madura Island Regions - Tjipto Haryono; Ika Rochdjatun Sastrahidayat; Gatot Mudjiono; Toto Himawan (The East Java Biological Society, 2016)
Madura is enriched by great diversity despite of its infertile natural condition. This condition influences fruit flies existence and diversity. Purpose of this study was to investigate the diversity and distribution of fruit flies with their host in Madura region. Sampling methods in this study were fruit host collection (rearing) and trapping using Steiner-type trap that were set in 48 locations in several villages in Bangkalan, Sampang, Pamekasan, and Sumenep regencies. Steiner traps were combined with 2 different attractants, such as methyl eugenol (ME) and Cue Lure (CL). There were 5 species of fruit flies obtained from trapping and rearing, namely Bactrocera carambolae, B. papayae, B. umbrosa, B. albistrigata, and B. cucurbitae. Results indicate that the distribution, diversity, and abundance of fruit flies were influenced by the diversity of fruit host, air temperature, and relative air humidity. It is also identified two species of parasitoid imago from rotten fruits collection, namely Biosteres vandenboschi and Fopius arisanus.